PEMANFAATAN SITUS SINGOSARI DALAM BANGKAN LITERASI SEJARAH PESERTA DIDIK - Zahroh, Nur Lailatus (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2014)
SMPI al Ma'arif is truly beneficial since it is located around the site Singosari, however the students in this schools do not know the history of the site Singosari; even they have never visited the historical object at all. In fact, the material about Singosari kingdom is one of the mandates of the national curriculum. To develop historical literacy as an effort to preserve the site and develop a sense of affection among the students towards historical site, the use of the Singosari site is the right step. The author is using qualitative research approach based on naturalistic studies. The research findings show that historical literacy development among the students by utilizing the historical sites have been reflected in the RPP made by the teacher. In practical aspect, some historical literacy index zas developed by a teacher. The development of historical literacy by utilizing the historical siteshas changed the paradigm of historical fact memorization to improve the students' involvement in historical sources.Keywords: The Uise of Singosari Site, Literacy Ffistory of Students